"One day visit": a predictable clinical procedure. (June 2022) - Tagliaferri, Dr. Davide; Ponzi, Dr. Armando
Abstract : Purpose: The present clinical case aims to introduce a cluster of techniques based on a digital and biological basis, to be used at intrasurgical time, in order to achieve a predictable clinical outcome. In fact, the possibility of merging data could allow a single-step procedure, introducing concepts like 'one day visit' with Socket shield (SS), implant and provisional crown, same-day delivery. This procedure is well accepted by the patient as reducing surgery sessions and prosthetic time. Methods: A CBCT and a digital impression were used for initial diagnosis, obtaining data about tooth anatomy, bone quality, and bundle bone extension. Surgical planning and relative stent, allowed a careful position of implant inter-radicularly to achieve best primary stability, required for an immediate load on the mandibular molar area. It was first performed an SS on molar #46, with a seagull wing configuration (i.e., maintaining a small septum area between vestibular roots laminae. The implant was positioned in the inter-radicular area using a safe surgical stent: IT, IT curve and the implant stability quotient (ISQ (>70) were measured establishing criteria for immediate loading. An intra surgical impression scan was taken using a T-Base system allowing the planning of an immediate digital provisional crown in 40 minutes. Meanwhile, the SS shoulder was reduced, root spaces were filled with bone chips mixed with Fibrin glue and covered with platelet-rich-fibrin (PRF) A large healing cap was inserted on waiting time. The provisional crown fit was excellent requiring minor adjustment, and was immediately positioned. Seven months later a digital crown copy on disilicate was inserted. Results: SS proved to maintain marginal gingiva and bundle bone. A novel intrasurgical action allows the implant stability measurement and immediate digital impression, picking high-quality prosthetic data.(time 0 concept. Follow-up shows crown stability and maintenance of both soft and hard tissue volume over 3 years. Conclusions: This is a proof of principle clinical case. Hardware & Software technologies were used to improve the predictability of outcome and stability over time of soft and hard tissue. Several activities were done at intra-surgical time and allowed to achieve unique data for prosthetic planning. The SS typically used on an anterior maxillary area was here used on posterior region and it is a fundamental step on 'single day visit' approach. The technique is operator sensitive and may not be applicable in any single case. More studies and clinical confirmation are therefore required.